Effect of meso Positioned Substituents on the Stability and Photodynamic Activity of Lipid‐Membrane‐Incorporated Porphyrin Derivatives. (30th March 2022) - Nishimura, Kotaro; Shimada, Risako; Yamana, Keita; Kawasaki, Riku; Nakaya, Toshimi; Ikeda, Atsushi
Abstract: In this study we prepared aqueous solutions of lipid‐membrane incorporated tetraarylporphyrins and tetrapyridylporphyrin (LMIPors) by the injection method using dimethyl sulfoxide. The porphyrins with proton‐donor groups at the meso position afforded stable aqueous solutions of LMIPors. However, although tetrakis(carboxyphenyl)porphyrin was scarcely incorporated in lipid membranes, it was soluble in water. Among these LMIPors, the photodynamic activity of tetrakis(hydroxyphenyl)porphyrin was higher than that of tetrakis(aminophenyl)porphyrin. This was attributed to the self‐aggregation of a part of tetrakis(aminophenyl)porphyrin in the liposomes, which induced self‐quenching and the consequent decrease of its photodynamic activity. Abstract : Aqueous solutions of lipid‐membrane‐incorporated tetrakis(hydroxyphenyl)porphyrin and tetrakis(aminophenyl)porphyrin prepared by the injection method using dimethyl sulfoxide were found to be highly stable, and the former exhibited higher photodynamic activity toward HeLa cells than did the latter.